Susceptibility of ten tomato cultivars to attack by Tetranychus evansi Baker & Pritchard (Acari: Tetranychidae) under laboratory conditions - Djossou, R.; Azandémè-Hounmalon, G.Y.; Onzo, A.; Gnanvossou, D.; Assogba-Komlan, F.; Tamò, Manuele (Springer, 2021)
We evaluated, in a laboratory experiment, the susceptibility of 10 tomato cultivars to the attack by the tomato red spider mite Tetranychus evansi, an invasive pest of this crop in Benin. Among the 10 cultivars tested, six were imported (i.e. Roma VF, Tima, Rio Grande, Buffalo, Petomech, and TLCV15) and four local (i.e. Akikon, Tounvi, TomL4, and Kèkèfo). Leaf disks (2.5 cm diameter) excised from leaves of tested cultivars, and placed upper side down on top of water-soaked cotton wool laying in 9.5 cm diameter Petri dishes (6 leaf disks per Petri dish), served both as experimental units and feeding source for the mites. Mites were individually placed on leaf disks of each cultivar and several biological parameters – development, reproductive parameters and longevity – were assessed. The experiments were performed at 27 ± 1 °C, 65–70% RH, and 12:12 h (L: D) photoperiod. Our results revealed significant effects of tomato cultivars on several biological parameters of T. evansi, especially the developmental time of the egg stage (P ˂ 0.0001), and the larval stage (P = 0.0113), as well as female oviposition period (P = 0.0002). Likewise, female longevity (P = 0.0095) and fecundity (i.e. egg/♀, P = 0.0055) were significantly affected. The sex-ratio of the progeny was generally similar for all the cultivars except for Buffalo and Tounvi on which most juveniles did not develop beyond the larval stage. These two cultivars appeared as potential tomato cultivars for implementation of IPM strategies for the control of T. evansi.